The effect of psychological contract on turnover intention among nurses: a meta-analytic review - Xianying Lu; Jing Yang; Dingxi Bai; Mingjin Cai; Wei Wang; Jiali He; Xiaoyan Gong; Chaoming Hou; Jing Gao (BMC, 2023)
Abstract Background The turnover intention (TI) of nurses is common, posing a threat to modern healthcare organizations. Psychological contract (PC) is a predictor of TI, affecting significantly nurse's TI. However, the extent of the association between PC and nurse's TI is unknown. We performed a meta-analysis to quantitatively analyze the relationship between PC and nurse's TI. Methods We searched nine electronic databases from inception to July 2023. Observational studies were included using a retrieval strategy related to PC and TI. Meta-analyses of common effect and random effect models were performed using R software with Spearman or Pearson correlation coefficients. Meta-regression, subgroup analysis, publication bias, and sensitivity analysis were also carried out . Results Eighteen studies including 8,908 nurses were identified. Based on various PC-related perspectives, 16 studies explored nurses' TI in terms of the content and three-dimensional structure of PC. Of these, 9 studies reported the negative direction of the correlation between PC and TI (r ranged from − 0.20 to -0.45), whereas 7 studies reported the positive direction of the correlation between PC and TI (r ranged from 0.32 to 0.50). The PC total and its dimensions were found to have moderately significant associations with TI, with the exception of the PCE and PCE-I. Additional, 2 studies reported the relationship between the outcome of PC and TI, the PCF, PCB, and PCV were powerful predictors of nurses' TI. Meta-regression and subgroup analysis found that only nurses working in specialized departments might be the source of heterogeneity. Conclusions To our knowledge, this was the first meta-analysis to quantitatively examine the relationship between PC and TI among nurses. The findings reaffirmed the necessity for healthcare administrators and the medical profession to valued nurse' good interpersonal, social support, humanistic environment, and meet nurses' psychological and spiritual needs in addition to their material demands. Moderators of the connection between PC and TI, based on meta-regression and subgroup analyses, should be carefully explored as they may aid in identifying nurses' TI. Additional, longitudinal research, as well as mixed research, should be conducted to more comprehensively explore the relationship between PC and TI.